From Metaphor to Metonym: Shakespearean Recognition in the United States University - Della Gatta, Carla (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This essay historicizes the Shakespeare curriculum at UC Berkeley’s English department over the last one hundred years. An elite research university in the United States, UC Berkeley’s extensive course offerings have expanded due to changes in undergraduate education and external cultural shifts. With a growing number of courses on sexuality, race, gender, etc., that became part of the purview of an English department, the teaching of Shakespeare expanded as well. I demonstrate how the emphasis on Shakespeare in the U.S. undergraduate curriculum shifts over time from one form of recognition—an acknowledgement of his value or worth—to a recognition of identifying with his work based on prior experience. Distinguishing between courses that combine “Shakespeare and” and those that combine “Literature and,” I expose the consequences each has for the canonicity of both Shakespeare and subject fields with which his works are placed in conversation, explicitly and implicitly. I argue that the expansion of Shakespeare in the American undergraduate curriculum coincides with and depends on the compression of key aspects of interpretation that pose challenges for the new knowledges it seeks to create. I illuminate how an expanded Shakespeare curriculum saw a compression of Shakespeare into metonymic mythic status, which has implications for the teaching of literature from various identity and cultural groups. I demonstrate how the origins of an expansive undergraduate Shakespeare curriculum in the United States positions Shakespeare as the interlocutor for a wide range of topics.